Kedudukan Memorandum Of Understanding Dalam Joint Venture Agreement Sebagai Bentuk Kerja Sama Penanaman Modal Asing - Muhammad Syaban Husein (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Increasing foreign investment in Indonesia through a joint venture cooperation scheme means that each party must lock a cooperation agreement through a Memorandum of Understanding (MoU). The aim of this research is to determine the position of the MoU in joint ventures in the context of foreign investment, especially in Indonesia. This writing uses normative juridical methods by conducting a literature review. The research results show that the position of the MoU in foreign investment cooperation through joint ventures is very significant, because almost every investment begins with the signing of the MoU. An MoU has a very important function for a joint venture, and practically its legal status is the same as other contracts that bind the parties.